Strategi Komunikasi Pemasaran Wisata Pantai Pasir Putih Parbaba Dalam Meningkatkan Kunjungan Wisatawan di Kabupaten Samosir - Haris, Abdul; Sihaloho, Arnelia; Andary, Ria Wuri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the efforts of the Pasir Putih Parbaba Beach tourism management in improving the marketing communication strategy of Pasir Putih Parbaba Beach tourism, to determine the inhibiting factors of the marketing communication strategy of Pasir Putih Parbaba Beach tourism in increasing tourist visits. This study discusses and presents a description of the data obtained through the results of field research through data collection methods that have been mentioned in the previous chapter. Here the author uses a descriptive method with a qualitative approach. Qualitative research is a research procedure that produces descriptive data in the form of words or spoken words from people and behavior can be observed.